To solve this, we first distribute and simplify each term within the parentheses:
1/2 * (x + 4) = (1/2 * x) + (1/2 * 4) = 1/2 * x + 2
1/4 * (4x - 2) = (1/4 * 4x) + (1/4 * -2) = x - 1/2
Now we can combine the two simplified terms:
(1/2 * x + 2) + (x - 1/2) = 1/2 * x + x + 2 - 1/2 = 3/2 * x + 3/2
The final answer in mixed number form is 3/2 * x + 3/2.
Add: 1/2 * (x + 4) + 1/4 * (4x - 2)
Answer should be in mixed number form. (1 pointAdd: 1/2 * (x + 4) + 1/4 * (4x - 2)
Answer should be in mixed number form. (1 point
3 answers
wrong
Wrong